MODERATE ISLAM IN LITERARY TEXTS BY K. H. MUSTOFA BISRI AND ITS RELEVANCE AS TEACHING MATERIALS AT SMAN 4 JEMBER - Shidiq Ardhianta (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
Radical Islamic teachings penetrated the world of education. This was also experienced at SMAN 4 Jember. Prevention efforts involving teachers are very important, including Indonesian language teachers. Indonesian language teachers can play a role through literary learning. The research focuses on two things, namely (1) what moderate Islam is taught by K. H. Mustofa Bisri's literature through his literary works? (2) How can K. H. Mustofa Bisri's teachings on moderate Islam be integrated into teaching materials at SMA 4 Jember? The literary analysis stage begins with reading, recording, and content analysis. The validity of the research data was tested through validity and reliability tests. The validity test used is semantic validity, while the reliability test uses intrarater reliability and interrater reliability. The results of this study are as follows. There are several poems and short stories of K. H. Mustofa Bisri which specifically contain moderate Islamic education. This moderation partly rejects the extreme left, as in the short story "Kang Maksum". Others, reject the extreme right understanding as in the poem "I miss you, O Muhammad, Gus Jakfar's short story, Mbok Yem, Eid is just a day away, Gus Muslih". Moderation is conveyed by indirect and entertaining delivery techniques. Literature which is full of moderate values ​​is very relevant to be used as teaching material at SMA 4 Jember which applies the 2013 curriculum. After observation and data mining, the Indonesian language learning curriculum contains literary studies. In general, the achievement goal of learning literature is more likely to instill positive values ​​that can shape character.